Evidence on the effectiveness of mosses for biomonitoring of microplastics in fresh water environment. (August 2018) - Capozzi, F.; Carotenuto, R.; Giordano, S.; Spagnuolo, V.
Abstract: Mosses are well known as biomonitors of fresh water for metal pollutants, but no studies were reported so far about their ability to intercept plastic particles, although this kind of pollution has become an urgent issue worldwide. In the present work, the interaction between the moss Sphagnum palustre L. cultured in vitro and polystyrene nanoparticles (NPs) was studied for the first time in a laboratory experiment, in the view of using moss transplants for detecting microplastics in fresh water environments. The ability of S. palustre to intercept and retain polystyrene, and the effects of vitality and post-exposure washing on NP retention by moss were tested. Fluorescence microscope observations showed that polystyrene NPs were retained by moss leaves in form of small (the most abundant fraction) and large aggregates. Particle count analysis highlighted that the number of particles increased while increasing the exposure time. Moreover, moss devitalization favored NP accumulation, likely because of cell membrane damages occurred in dead moss material. Post-exposure washing induced a loss of larger aggregates, suggesting that exposure time is a key point to be carefully evaluated in field conditions. These results encourage the use of S. palustre transplants for monitoring microplastics contamination of fresh water environments. Graphical abstract: Image 1 Highlights: The ability of S. palustre to intercept and retain polystyrene NPs was tested. S. palustre retained NP aggregates more in devitalized than in living moss. NP entrapped increased while increasing the exposure time. Post-exposure washing induced a loss of larger aggregates. Particle count showed that small aggregates were the most abundant.